Building more resilient food systems: Lessons and policy recommendations from the COVID-19 pandemic - McDermott, John; Allison-Reumann, Laura (International Food Policy Research Institute, 2022)
Two years in, the long-term health and economic effects of the COVID-19 pandemic continue to influence poverty, food systems, and food security. Drawing on CGIAR research on the COVID-19 pandemic thus far, this brief presents key lessons learned and policy recommendations to inform decision-making processes around managing risks, addressing structural vulnerabilities, and building resilient and sustainable food systems.